Factors Affecting Fraud Prevention: The Role of Internal Audit, Organizational Culture, and Whistleblowing System - Nurizal AR, Muhammad; Cris Kuntadi; Prita Yuniarti Ramayani (Dinasti International Journal of Digital Business Management, 2023)
This article discusses the factors that affect Affecting Fraud Prevention as the dependent variable. The variables the role of internal audit, organizational culture and whistleblowing system as independent variables that influence it, this study is a literature review that describes the influence of the role of internal audit, organizational culture and whistleblowing system on Affecting Fraud Prevention, this article is a study in applied administration to increase the literacy of the influence between variables for further research purposes. The results of the literature review are the role of internal audit, organizational culture and whistleblowing system affect Affecting Fraud Prevention.